PERKAWINAN ANAK DI BAWAH UMUR DALAM PERSPEKTIF MAQASHID AL–USROH: Studi Kasus di KUA Kecamatan Wonosalam Kabupaten Jombang - M. Qomar; Abd. Basit Misbachul Fitri (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Marriage, a sunnah of the Prophet, should align with maturity standards, as outlined in Law Number 16 of 2019, Article 7, which sets the minimum marriage age at 19 for both men and women. However, the Compilation of Islamic Law (KHI) stipulates a minimum age of 19 for men and 16 for women, allowing marriages below these ages if a marriage dispensation is obtained from the Religious Court. In 2020, records from the Wonosalam District Religious Affairs Office showed that 22 out of 282 marriages involved such dispensations. This study, using interviews and documentation, analyzed early marriage cases through a descriptive method. Findings suggest that underage marriage should not be justified solely by one maqashid value, such as avoiding adultery. Marriage should ensure the fulfillment of multiple maqashid values, including hifz al-nafs (protection of the soul), hifz al-mal (protection of wealth), hifz al-'aql (protection of intellect), and hifz al-din (protection of religion). The practice of early marriage should be carefully evaluated, considering both its benefits and drawbacks in light of maqashid principles. Focusing on a single maqashid value while neglecting others contradicts the comprehensive message of the Qur'an, which emphasizes the balance of maslahah (benefit) and mafsadat (harm). Thus, underage marriage requires a thorough consideration of all relevant aspects to uphold the Qur'anic ideals.